STRATEGI PEMASARAN PARIWISATA PASCA PANDEMI: KESIAPAN DAN KOMPETENSI PRODUKSI VIDEO PARA PEGIAT WISATA DI KABUPATEN BATANG - Naryoso, Agus; Hasani, Mj Rizqon (Interaksi: Jurnal Ilmu Komunikasi, 2023)
The Batang Regency Government has launched the Batang Visit Year 2022 since 2017. This is an effort of the Batang Regency Government to improve the community's economy in the tourism sector. The Batang Regency Government has also renovated several tourist attractions that attract tourists. Problems arise when Indonesia is hit by the corona outbreak which also hit the tourism sector. After the corona pandemic ended, the tourism sector recovered, but needs huge promotions, including producing tourism video by local tourism communities. The research aims to determine post-pandemic tourism marketing strategies, especially the readiness and video production competence of Batang Regency tourism activists. The research used a qualitative approach and descriptive analysis methods with research subjects being tourism activists in the Pandansari Tourism Activist Community, Blado District, Batang Regency, Batang Regency. The results of the research show that tourism activists in Batang Regency already have the readiness and competence to produce tourism videos, both from the planning process, shooting execution to image editing, including using videos as tourism promotional material according to the chosen promotional media platform. Tourism activists have also produced video works that can be seen on the Batang district tourism community media account.